Analysis of associations between selected sports performance factors and racing performance in the youth alpine skiing category - Turkova, Ivana; Heidler, Josef; Nosek, Martin (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The research focuses on the analysis of associations between important motor skills that are essential for alpine skiing and performance in the youth category. The study came about in response to the fact that associations between individual concepts of motor abilities and performance in alpine skiing are not clearly described in the literature. Aim of Study. The research aimed to evaluate and identify possible associations between selected factors of sports performance, and actual performance of youth alpine skiers. Material and Methods. A group of 12 elite female Czech youth skiers (16-18 years old) was monitored for their training indicators, racing season performance, and selected sports performance factors (anthropometry, balance, laterality, muscle condition). To evaluate associations of monitored parameters, Spearman’s correlation coefficient r was used. Results. The results of multiple analyses show no statistically significant correlation between anthropometric features and total FIS race performance. On the other hand, a statistically significant dependence was noted for specific training indicators (skiing hours, gate skiing) and FIS race performance. In the analysis of performance and monitored parameters (laterality, balance) of youth skiers no statistical dependence was found. Thus it may be assumed that the balance on both the dominant and non-dominant leg was the same, although muscle imbalances were identified among the skiers. Conclusions. From the obtained knowledge, we can state that alpine skiing is a complex sport, in which there is no unilateral overloading of the organism. To obtain excellent and steady results during a competition all the examined variables are more or less important for skiers. Without these abilities and skills, skiers’ performance will never reach the maximum. Even though conditioning and skills are one of the main features of skiing, we should not forget about regeneration and compensation to prevent a risk of potential muscle imbalances or injuries among young athletes.
Keywords: balance; anthropometrics; alpine skiing; FIS score; muscle imbalances; lower limb laterality